Foundations of Advanced Neuroanatomy: Technical Guidelines for Specimen Preparation, Dissection, and 3D-Photodocumentation in a Surgical Anatomy Laboratory - Leonel, Luciano César PC; Carlstrom, Lucas P.; Graffeo, Christopher S.; Perry, Avital; Pinheiro-Neto, Carlos Diogenes; Sorenson, Jeffrey; Link, Michael J.; Peris-Celda, Maria (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This study was aimed to provide a key update to the seminal works of Prof. Albert L. Rhoton Jr., MD, with particular attention to previously unpublished insights from the oral tradition of his fellows, recent technological advances including endoscopy, and high-dynamic range (HDR) photodocumentation, and, local improvements in technique, we have developed to optimize efficient neuroanatomic study.Methods Two formaldehyde-fixed cadaveric heads were injected with colored latex to demonstrate step-by-step specimen preparation for microscopic or endoscopic dissection. One formaldehyde-fixed brain was utilized to demonstrate optimal three-dimensional (3D) photodocumentation techniques.Results Key steps of specimen preparation include vessel cannulation and securing, serial tap water flushing, specimen drainage, vessel injection with optimized and color-augmented latex material, and storage in 70% ethanol. Optimizations for photodocumentation included the incorporation of dry black drop cloth and covering materials, an imaging-oriented approach to specimen positioning and illumination, and single-camera stereoscopic capture techniques, emphasizing the three-exposure-times-per-eye approach to generating images for HDR postprocessing. Recommended tools, materials, and technical nuances were emphasized throughout. Relative advantages and limitations of major 3D projection systems were comparatively assessed, with sensitivity to audience size and purpose specific recommendations.Conclusion We describe the first consolidated step-by-step approach to advanced neuroanatomy, including specimen preparation, dissection, and 3D photodocumentation, supplemented by previously unpublished insights from the Rhoton fellowship experience and lessons learned in our laboratories in the past years such that Prof. Rhoton's model can be realized, reproduced, and expanded upon in surgical neuroanatomy laboratories worldwide.
Keywords: skull base; endoscopy; imaging; three-dimensional photography; dissection; anatomy; neuroanatomy; education